DEVELOPMENT OF DOMINO CARD MEDIA TO INCREASE LEARNING MOTIVATION OF CLASS V ELEMENTARY SCHOOL STUDENTS - Rini Susdamayanti (Renjana Pendidikan Dasar, 2022)
The purpose of this study is determine the feasibility of domino card learning media in thematic learning and find out the suitability of domino cards to increase learning motivation of fourth grade elementary school students. This research is development research using the Borg and Gall model. The research was conducted at SDN Lomaer 1with the subject of 16 fourth grade students. The results showed the feasibility of domino card learning media based on material validation, media validation, group response trials and large group student response trials getting an average rating of 89% with very valid qualifications. The results of student learning motivation in small groups showed the percentage before 58% with enough categories, after the percentage of 89% with very high category. The results of student learning motivation in large groups showed before the percentage of 39% with the low category and after percentage of 76% with high category. Based on the data mentioned above, it can be concluded that the domino card learning media is suitable for use in the learning process and can increase the learning motivation of grade V SD students.